Cistercians: Wine Makers to the World - Truax, Jean (Cistercian studies quarterly, 2024)
The article focuses on the monastic order Cistercians' significant contributions to the wine industry, particularly their involvement in the creation and cultivation of various grape varieties and wine regions. Topics include the development of Chablis and other key wines, the concept of terroir and its commercial application, and the Cistercians' role in the expansion and refinement of viticulture through their land acquisition strategies and agricultural practices.